On Meromorphic Functions Defined by a New Class of Liu-Srivastava Integral Operator - Syed Ghoos Ali Shah (International Journal of Analysis and Applications, 2020)
In this work, we introduce and explore certain new subclasses of meromorphic functions. We aim to study some important properties such as coefficient estimates, growth rate and partial sums for these newly defined subclasses. It is important to mentioned that our results are generalization of number of existing results.